PENGARUH SENAM YOGA TERHADAP INTENSITAS DISMENORE PADA REMAJA PUTRI - Rauda, Rauda; Harahap, Novy Ramini; Aisyah, Siti; Putri, Ade Ilma Ilham (Universitas Murni Teguh, 2025)
Dysmenorrhea is characterized by lower abdominal pain that occurs before or during menstruation. It is one of the most frequent gynecological complaints among adolescents and often disrupts their daily activities, including school attendance and productivity. Non-pharmacological interventions, such as yoga exercise, have gained increasing attention as complementary approaches for managing menstrual pain. Yoga is believed to promote relaxation of the endometrial and pelvic muscles and stimulate the release of endogenous analgesic substances, including endorphins and enkephalins, thereby reducing dysmenorrheic symptoms. This study employed a quasi-experimental design using a pretest–posttest approach with a non-equivalent control group. The sample was divided into two groups: an intervention group and a control group. The intervention consisted of yoga exercises performed for three consecutive days. Dysmenorrhea intensity was measured using the Wong–Baker Faces Pain Rating Scale. Data analysis was conducted using the Wilcoxon test and the Mann–Whitney test due to the non-normal distribution of the data. A significant decrease in pain intensity was observed in the intervention group following the yoga exercise program (p = 0.004). The control group also showed a statistically significant change (p = 0.006), although the reduction was not as substantial. Comparative analysis between the two groups indicated a significant difference in pain reduction (p = 0.015), demonstrating the stronger influence of the yoga intervention compared to no intervention.Discussion:The findings suggest that yoga exercise is effective in reducing dysmenorrhea intensity among adolescent girls. The physiological mechanism behind this improvement may be attributed to muscle relaxation, enhanced blood circulation, and the increased release of endogenous opioid peptides such as endorphins and enkephalins. These mechanisms collectively contribute to the reduction of menstrual pain. The results align with existing literature supporting yoga as a beneficial non-pharmacological approach for menstrual discomfort. This study concludes that yoga exercise has a significant positive effect on reducing dysmenorrhea intensity in adolescent girls. Yoga may be considered a practical, accessible, and safe complementary therapy for managing menstrual pain among adolescents. Abstrak Dismenore adalah kondisi nyeri pada perut bagian bawah yang muncul sebelum atau selama periode menstruasi. Dismenore keluhan yang sering dialami remaja sehingga mengganggu aktivitas sehari-hari. senam yoga merupakan salah satu metode non-farmakologis yang dapat digunakan untuk mengurangi dismenore. Senam Yoga dapat merelaksasi otot – otot endometrium dan dapat merangsang tubuh untuk melepaskan senyawa penghambat disminore seperti endorphin dan enkefalin. Penelitian ini bertujuan untuk mengetahui pengaruh senam yoga terhadap intensitas dismenore pada remaja putri. Desain penelitian ini menggunakan Quasi experiment menggunakan pendekatan pretest-posttest with non-equivalent control group. Sampel pada penelitian ini dibagi 2 yaitu kelompok intervensi dan kontrol. Senam yoga dilakukan selama 3 hari berturut-turut. Pengukuran intensitas dismenore menggunakan Wong-Baker Faces Pain Rating Scale. Analisis data menggunakan uji Wilcoxon dan Mann-Whitney karena data tidak terdistribusi normal. Hasil penelitian menunjukkan adanya penurunan intensitas nyeri yang signifikan pada kelompok intervensi (p=0,004), sedangkan pada kelompok kontrol diperoleh nilai (p=0,006). Dengan Hasil uji beda menunjukkan adanya perbedaan yang signifikan antara kelompok intervensi dan kontrol (p=0,015). Kesimpulan dalam penelitian ini terdapat pengaruh signifikan senam yoga terhadap penurunan intensitas dismenore pada remaja putri.